You Don't Need to Run Every Eval - Zeng, Yuchen; Papailiopoulos, Dimitris (arXiv, 2026)
A modern model release reports scores on 40+ benchmarks and the same evaluations were run many more times before it: to track training progress, compare design choices, and select the checkpoint for the release. But do we need to run every eval? We compile a public score matrix of 84 frontier models on 133 benchmarks (2,604 cells, 23.3% filled) and find it is approximately rank-2: a model's scores across all 133 benchmarks are largely determined by just two numbers. We confirm this in two ways: scores hidden from the matrix are best recovered using two factors, and two factors already explain over 90% of the variation among models on the benchmarks they share. Building on this, we design BenchPress: a logit-space rank-2 matrix completion method that recovers held-out scores to within 4.6 points, and a confidence layer that says when each prediction can be trusted. Using BenchPress, we find a subset of five benchmarks [GPQA-D, HLE, Codeforces, MMLU-Pro, ARC-AGI-1] that can recover the rest of a model's public scorecard to within 3.93 points. For a tighter inference budget, a cheaper set [GPQA-D, MMLU-Pro, Aider Polyglot, MATH-500, AIME 2026] can predict a model's evals to within 4.55. We release the score matrix, the BenchPress code, and an interactive tool that predicts any model's score on any benchmark.